Modified TiO2 based photocatalysts for improved air and health quality - Vassilios Binas; Danae Venieri; Dimitrios Kotzias; George Kiriakidis (Journal of Materiomics, 2017)
Photocatalysis with modified titania is a promising approach to improve both air and health quality. Modified titania with novel photocatalytic properties under indoor light irradiation leads to smart coatings, which are benchmark materials suitable for their indoor applications. It is generally accepted that the photocatalytic activity is affected by the light absorption, charge creation/recombination rate and surface reactivity. In this contribution we focus on modified TiO2 as catalyst in heterogeneous photo-catalytic processes and address the efficiency of TiO2-based building and construction materials on the removal of environmental pollutants indoors and outdoors. We also present data on the presence of eventually formed, toxicologically relevant and harmful by-products as the result of the photo-induced degradation of pollutants in an effort for better evaluation of induced risks for human health from the application of TiO2 modified materials. Finally, we present recent results on the disinfection performance of these material and the inactivation of severe pathogens contained in water and indoor air environments.